Seniority wages and the role of firms in retirement - Wolfgang Frimmel; Thomas Horvath; Mario Schnalzenberger; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2015)
In general, retirement is seen as a pure labor supply phenomenon, but firms can have strong incentives to send expensive older workers into retirement. Based on the seniority wage model developed by Lazear (1979), we discuss steep seniority wage profiles as incentives for firms to dismiss older workers before retirement. Conditional on individual retirement incentives, e.g., social security wealth or health status, the steepness of the wage profile will have different incentives for workers as compared to firms when it comes to the retirement date. Using an instrumental variable approach to account for selection of workers in our firms and for reverse causality, we find that firms with higher labor costs for older workers are associated with lower job exit age.
Keywords: J14; J26; J31; H55; 330; retirement; seniority wages; firm incentives